A Case Report of Pediatric Colorectal Carcinoma in an 11-year-old Indonesian - Pahlevi Adeputra Nasution, Iqbal; Fikri, Erjan; Dutra Pratama, Raka (Indonesian Journal of Cancer, 2023)
Introduction: Colorectal carcinoma (CRC) is a rare condition among pediatric patients and is often considered the last possible diagnosis in individuals with defecating issues. Therefore, this case report aims to present and elaborate on the identification of pediatric CRC in a center in Indonesia.Case Presentation: An 11-year-old female adolescent presented with obstipation for a week after a series of defecating difficulty episodes spanning the last three months. Furthermore, these difficulties had been progressively worsening over the past two weeks. The patient also reported recurrent colic pain in the abdominal region, but the exact location was unspecified. Positive results of goat-like stool were found for three months, without any observed diarrhea episodes and blood or mucous layer on the stool. A significant weight loss of ±10 kg was reported during the illness period. On physical examination, symmetrical abdominal distention was observed, and colon-in-loop and CT assessment results supported this. These diagnostic measures showed a malignant-suggestive mass ascending to the transverse colon. A right extended hemicolectomy procedure was then carried out as the definitive treatment, accompanied by stoma ileocolostomy to divert defecation. The histopathological analysis on the 4.0 x 4.0 cm intraluminal mass confirmed the presence of poorly differentiated adenocarcinoma. Conclusion: The identification of chronic constipation among pediatric patients must raise awareness regarding the potential for mechanical bowel obstruction due to a malignant mass, specifically in inpatients.